2017
DOI: 10.1371/journal.pone.0172772
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between pickiness and subsequent development in body mass index and diet intake in obesity prone normal weight preschool children

Abstract: BackgroundMost children have periods in their life where they reject familiar as well as non-familiar food items and this is often referred to as pickiness. The consequences of pickiness may be malnutrition and, if prolonged, potentially lower body weight. However, studies investigating the consequence of pickiness on subsequent changes in diet intake and weight are limited.ObjectivesTo examine whether pickiness influences body mass index as well as diet intake over subsequent 15 months among obesity prone nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 27 publications
0
25
0
4
Order By: Relevance
“…Further, we have data on picky eating behaviour again in the same children 15 months later. The intervention did not show any effects on picky eating behaviour [ 13 ], thus we use data on picky eating behaviour from the 15 months follow-up to investigate if eating behaviour changed over time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we have data on picky eating behaviour again in the same children 15 months later. The intervention did not show any effects on picky eating behaviour [ 13 ], thus we use data on picky eating behaviour from the 15 months follow-up to investigate if eating behaviour changed over time.…”
Section: Methodsmentioning
confidence: 99%
“…Children that tend to have picky eating behaviours often have a lower diet quality [ 10 ], eat less fruit and vegetables [ 11 14 ] and have higher intakes of sugary foods and drinks [ 15 ]. The consequences of pickiness can be malnutrition and may, if prolonged, have an impact on weight development and risk of overweight and obesity [ 16 ], even though not all studies have observed this association [ 13 ]. The acceptance of healthy food choices later in childhood seems associated with breastfeeding duration independent of socio-economic status (SES) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…15 studies in this review included children younger than 17 years old, 5 of these were cohort studies. Our finding that severe or persistent picky eating is associated with increased odds of underweight suggests that these studies are describing different eating behaviors than many of the other studies like a recent article by Rohde et al (Rohde et al, 2017). A study conducted in China said that small children with picky eating and heavy low-for-height behaviors have a less optimal diet and are at risk of significant food and nutritional deficiencies (Volger et al, 2017).…”
Section: Discussionmentioning
confidence: 78%
“…The qualitative data suggested greater self-efficacy specific to picky eating in positive deviants. Recent longitudinal data on picky eating in early childhood and subsequent weight status have not shown a consistent relationship, although these studies were not done in a Latino population [ 46 , 47 ]. A recent study in a low-income, mixed race, preschool population found no association between picky eating and obesity but did find an association with healthy eating patterns and picky eating [ 48 ].…”
Section: Discussionmentioning
confidence: 99%